The diversity and variability of star formation histories in models of galaxy evolution. Issue 1 (25th July 2020) - Iyer, Kartheik G; Tacchella, Sandro; Genel, Shy; Hayward, Christopher C; Hernquist, Lars; Brooks, Alyson M; Caplar, Neven; Davé, Romeel; Diemer, Benedikt; Forbes, John C; Gawiser, Eric; Somerville, Rachel S; et al.
ABSTRACT: Understanding the variability of galaxy star formation histories (SFHs) across a range of time-scales provides insight into the underlying physical processes that regulate star formation within galaxies. We compile the SFHs of galaxies at z  = 0 from an extensive set of models, ranging from cosmological hydrodynamical simulations (Illustris, IllustrisTNG, Mufasa, Simba, EAGLE), zoom simulations (FIRE-2, g14, and Marvel/Justice League), semi-analytic models (Santa Cruz SAM) and empirical models (UniverseMachine), and quantify the variability of these SFHs on different time-scales using the power spectral density (PSD) formalism. We find that the PSDs are well described by broken power laws, and variability on long time-scales (≳1 Gyr) accounts for most of the power in galaxy SFHs. Most hydrodynamical models show increased variability on shorter time-scales (≲300 Myr) with decreasing stellar mass. Quenching can induce ∼0.4−1 dex of additional power on time-scales >1 Gyr. The dark matter accretion histories of galaxies have remarkably self-similar PSDs and are coherent with the in situ star formation on time-scales >3 Gyr. There is considerable diversity among the different models in their (i) power due to star formation rate variability at a given time-scale, (ii) amount of correlation with adjacent time-scales (PSD slope), (iii) evolution of median PSDs with stellar mass, and (iv) presence and locations of breaks in the PSDs. The PSD framework is a useful space to study the SFHs of galaxies since model predictions vary widely. Observational constraints in this space will help constrain the relative strengths of the physical processes responsible for this variability.